Delay in the diagnosis of esophageal carcinoma: Experience of a single unit from a developing country - Samarasekera, D.N. (My University, 2010)
Objectives : Main objective was to analyze the time delay between the onset of symptoms and the histological diagnosis of esophageal cancer. The subsidiary objective was to analyze the relationship between the time delay and stage of the disease at the time of definitive treatment. Study Design , Setting , and Methods : A prospective analysis of patients with esophageal cancer presenting to a single unit over a period of 24 months was performed. Interval from the onset of symptoms to the histological diagnosis and stage at presentation was analyzed. Results : There were 48 patients (male = 26) with a median age of 59.5 (range 43 - 84) years. First symptom was progressive dysphagia in all patients. Subsidiary symptoms were, weight loss in 83.3% (n = 40), abdominal / chest pain in 10 (20.8%), regurgitation in 14 (29.2%), odynophagia in three (6.2%), abdominal discomfort in two (3%), and dyspepsia in two (3%). The mean delay from the appearance of the first symptoms to the end point was 14.9 weeks (range 3 - 37 weeks). Total delay was due to patient delay in 82%, endoscopy delay in 7%, and delay in histological diagnosis in 11%. Conclusions : As the majority (82%) in our study showed patient delay, a community education program may help in their early presentation to the hospital. However, there is also a notable delay in endoscopy and histology (15%) services, mainly due to a shortage of endoscopy units and qualified histopathologists in the state sector.